Regeneration of HDTMA-modified minerals after sorption with chromate anions. Issue 57 (7th December 2016) - Thanos, A.G.; Sotiropoulos, A.; Malamis, S.; Katsou, E.; Pavlatou, E.A.; Haralambous, K.J.
Abstract: Surfactant-modified minerals have been widely used for the sorption of anionic and non-polar organic contaminants. This paper investigates the regeneration of various hexadecyltrimethylammonium bromide (HDTMA)-modified natural minerals saturated with chromate anions using different solutions for the extraction of chromates that has been sorbed at optimum conditions. The examined minerals include HDTMA-modified zeolite (clinoptilolite), exfoliated vermiculite, bentonite and attapulgite (palygorskite). Deionized water and sodium chloride, potassium chloride and sodium cyanide solutions at different concentrations (0.1–3 M) were employed as chromate desorption solutions. The HDTMA/Cr(VI)-mineral type, the desorbing solution type and its concentration and the mineral–solution contact time are key parameters that affect the process. From our results it was deduced that regeneration and reuse of HDTMA-modified minerals saturated with chromate is feasible. Bentonite exhibited greater stability than the other minerals studied in adsorption/desorption processes, maintaining 73% of its initial adsorption capacity after 14 successive regeneration cycles. The regeneration performance of the examined minerals follows the order: Bentonite > Attapulgite > Zeolite > Vermiculite. Kinetic study revealed that desorption was faster than adsorption, while the pseudo-second-order equation simulated better the experimental data.